Selection and outcome of implantable cardioverter‐defibrillator patients with and without cardiac resynchronization therapy: Comparison of 4384 patients from the German Device Registry to randomized controlled trials. (23rd January 2022) - Köbe, Julia; Willy, Kevin; Senges, Jochen; Hochadel, Matthias; Kleemann, Thomas; Spitzer, Stefan G.; Andresen, Dietrich; Jehle, Joachim; Steinbeck, Gerhard; Szendey, Istvan; Butter, Christian; Brachmann, Johannes; et al.
Abstract: Background: Registry data add important information to randomized controlled trials (RCT) on real‐life aspects of implantable cardioverter‐defibrillator (ICD) patients with and without cardiac resynchronization therapy (CRT‐D). This analysis of the prospectively conducted German Device Registry aims at comparing mortality rates, comorbidities, complication rates to results from RCT. Methods: The German Device registry (DEVICE) prospectively collected data on ICD and CRT‐D first implantations from 50 German centres. Demographic data, details on cardiac disease, electrocardiogram (ECG), medication, and data about procedure, complications, and hospital stay were stored in electronic case report forms. One year after device implantation patients were contacted for follow‐up. Results: DEVICE included n = 4384 first ICD/CRT‐D implantations (29.3% CRT‐D devices). We found a strong adherence to guidelines with over 90% of patients being on ß‐blocker and ACE‐inhibitor medication and adequate QRS width in the majority of CRT‐D patients. Patients receiving a CRT‐D were older (67.6 ± 11.0 years vs. 63.9 ± 13.4 years, p < .001) and had lower ejection fractions (mean 25% vs. 30%, p < .001) compared to ICD patients. Dilated cardiomyopathy was the predominant underlying heart disease in CRT‐D (53.3%), coronary artery disease in ICD patients (64.7%). Compared to RCT our DEVICE patients had more comorbidities (17.9% chronic kidney disease [CKD]) and higher 1‐year mortality rates (10.7% ICD group, 12.3% CRT group). In multivariate analysis, CKD patients had an almost 2‐fold higher risk of 1‐year mortality. Conclusion: Despite relevant limitations of registry data, DEVICE highlights important differences between RCT and real‐world registry data and the impact of comorbidities on mortality of ICD and CRT‐D recipients.